Complications of delayed reconstructive and plastic surgery after radical mastectomy - A. D. Zikiryakhodzhaev; V. V. Efanov; F. N. Usov; M. M. Ismailova (ABV-press, 2015)
Objective: to assess the nature and frequency of complications due to different types of delayed reconstructive and plastic surgery (DRPS) after radical mastectomy (RME).Subjects and methods. The investigators analyzed the results of treating 31 patients after RME in 2001 to 2014. DRPS was performed 4 months to 15.5 years (more frequently 1 to 3 years) following RME. To choose an optimal reconstructive method, it should be kept in mind the following factors: breast size and ptosis, the patients' somatic status, the presence of scars in the donor area, and radiotherapy to the chest. The breast was repaired using a TRAM flap in 22 patients. Eight cases underwent two-step reconstruction, by setting a tissue expander at Step 1 and replacing it by a silicone implant at Step 2. In one patient, a Becker expander/implant was used as a plastic component for delayed breast reconstructionin order to make a bed with a latissimus dorsi fragment.Results. Complications were observed in 8 (25.8 %) patients. The largest number of complications occurred in 6 cases after breast reconstruction using a TRAM flap. There were complications, such as inferior epigastric arterial thrombosis; marginal necroses of a displaced TRAM flap; hematoma in the postoperative wound region; implant bed infection; and wound edge diastasis in the donor area. In virtually all complicated cases, the patients received multimodality (75 %) and combined (12.5 %) treatments before DRPS.Conclusion. Beam radiotherapy and chemotherapy increase the risk of complications after both reconstructive plastic surgery with implants and the use of autologous tissues. Two-step reconstruction applying implants provided a good cosmetic effect and the least rate of complications.